تأثير درجات الملوحة المختلفة في نمو أمهات أسماك المشط الأزرق Oreochromis aureus (Latakia University Journal -Biological Sciences Series, 2013)
تمَّ تربية الأمهات سمك المشط الأزرق (Oreochromis aureus)في أحواض زجاجيّة في المعهد العالي للبحوث البحريّة بهدف دراسة تأثير اختلاف درجات الملوحة على معدّلات نمو هذه الأمهات ومقارنة النتائج مع تلك التي تم الحصول عليها في البيئة الطبيعيّة. نُقلت الأمهات من مزرعة أسماك مصب السّن (بانياس) إلى أحواض التجربة في بداية شهر نيسان2011، وبعد أقلمتها تدريجيّاً إلى ثلاث درجات ملوحة (7‰، 14‰، 19‰) في ثلاثة أحواض (خصص الحوض الرابع كشاهد: مياه عذبة).  تمّ تغذيتها مرّتين يوميّاً حتّى الشبع لمدّة 72 يوم على عليقة حاوية 35% بروتين خام.  أظهرت النتائج أنّ الأسماك المربّاة تحت درجة الملوحة 14‰ أعطت أفضل معدّل نمو وزني، حيث بلغ الكسب بالوزن 18.76غ/سّمكة بمعامل تحويل غذائي 2.04 وعن الأسماك المربّاة تحت الدّرجة 7‰ بلغ الكسب بالوزن 17.16غ/سّمكة بمعامل تحويل غذائي 2.51، أمّا الأسماك المربّاة في المياه العذبة فقد بلغ الكسب بالوزن 14.63غ/سّمكة بمعامل تحويل غذائي2.97 في حين أعطت الأسماك المربّاة تحت الدّرجة 19‰ أقل كسب بالوزن 9.24 غ/سّمكة بمعامل تحويل غذائي 3.7. The broodstock of Blue tilapia (Oreochromis aureus) were reared in glass aquaria in the laboratory of the High Institute of Marine Research to study the effect of different water salinities on growth rates of those broodstocks and comparing the results with those obtained from the natural environment (freshwater). The broodstock were transported from El-Sin Fish Farm- Banias to the culture aquaria at the beginning of April (2011).  After acclimation to the three studied water salinities (7‰, 14‰ and 19 ‰) in three aquaria (the forth aquarium was left as a control: fresh water), the fish were fed on a diet containing 35 % protein till satiation, twice a day for 72 days. The results revealed that the broodstock reared at 14‰ Salinity produced the best weight gain, where the weight gain was 18.76 g/fish with a feed conversion rate (FC) of 2.04.  The weight gain was 17.16 g/fish for the fish reared at 7‰ with a FC= 2.51, while broodstock reared at fresh water gained 14.63g/fish with a FC= 2.97.  The worst weight gain was obtained from the broodstock reared at 19‰ (9.24 g/fish) with a FC= 3.7.